Structural engineering of non-layered 2D materials - Yang, Jiefu (Nanyang Technological University, 2024)
This thesis investigates advanced materials, specifically delving into the realm of non-layered two-dimensional (2D) materials and their potential for structural engineering. Innovative methodologies are employed to gain fresh insights into material synthesis, structural modification, and properties tunings. The ensuing chapters reveal groundbreaking discoveries, which collectively redefine our understanding of the intricate interplay between structural nuances and material properties within non-layered 2D materials.